Evaluation of Uncertainties in lung measurements of actinides due to counting statistics. (January 2019) - Nadar, M.Y.; Akar, D.K.; Singh, I.S.; Sawant, P.D.; Kulkarni, M.S.
Abstract: Counting statistics is an important parameter that can introduce uncertainties in the lung activity measurements of actinides in radiation workers. Evaluation of uncertainties due to counting statistics is practically difficult as it requires monitoring various radiation workers having different levels of lung actinide content, multiple times, each for 50 min of monitoring period. However, different activities in lungs can be simulated by combining uncontaminated male data with LLNL phantom data acquired with 241 Am and natural uranium lung sets at various short periods. Therefore, multiple measurements were carried out on realistic thorax LLNL phantom with 241 Am and natural uranium lung sets for 15–600 s. The mean counts with the phantom at various time intervals, corresponds to different actinide activities in lungs, assuming they are obtained for 50 min of monitoring interval. Using propagation of error, standard deviations were evaluated for combined phantom and uncontaminated adult male data. The combined standard deviations and mean phantom counts are used to evaluate scattering factors (SFs) for uncertainties due to counting statistics for Phoswich and HPGe array detectors. The SFs due to counting statistics are found to be the function of lung activities of radionuclides as well as energies and yields of the photons emitted by radionuclides. SFs are found to increase with decrease in lung activity. For similar yields photons, SFs are found to be lower for higher energy photons compared to lower energy photons. For photons of similar energies, the SFs are lower when yield is higher compared to lower yield photons. Highlights: Uncertainties due to counting statistics are evaluated as a function of activities of 241 Am and natural uranium in lungs. Uncertainties are found to be function of activity in lungs, energy and yield of photons emitted by radionuclides. Uncertainties are found to be inversely proportional to deposited lung activity. For similar yield photons, uncertainties are found to be lower for high energy photons. For similar energies, uncertainties are lower for high yield photons.